An alternative strategy for enhancing stability and antimicrobial activity of catechins by natural deep eutectic solvents. (January 2022) - Zhou, Pengfei; Tang, Daobang; Zou, Jinhao; Wang, Xuping
Abstract: The low stability and loss of antimicrobial activity of catechins limited their application in food preservation. In this study, four kinds of catechins including (−)-epicatechin (EC), (−)-epigallocatechin (EGC), (−)-epicatechin-3-gallate (ECG), and (−)-epigallocatechin-3-gallate (EGCG) were selected as model compounds. Natural deep eutectic solvents (NADES) are a new generation of green solvents that have attracted much attention due to their unique characteristics. The effects of NADES on the stability and antimicrobial activity of catechins were investigated in the present study. Eight typical NADES, especially choline chloride/glycerol (ChG), were found to significantly enhance the thermal and storage stability of catechins. This finding accounted for by hydrogen bonding network formation between ChG and catechins, confirmed by FT-IR and 2D NMR analysis. Additionally, ChG decreased the minimum inhibitory concentration of catechins on Gram-positive and Gram-negative bacteria, which may be associated with its stabilizing property. The stability of catechins combined with NADES revealed their potential of applications in the food industry. Graphical abstract: Therefore, this study aimed to investigate the effects of the NADES on the stability of catechins at different temperatures and explore the stabilizing mechanism of NADES on catechins by NMR and FT-IR. Finally, the antimicrobial activity of catechins dissolved in NADES and water were comparatively studied. This work represented a novel approach substantiating the role of NADES as green additive to enhance the stability of bioactive compounds. Highlights: NADES significantly enhanced the thermal and storage stability of catechins. The strong hydrogen bonding network was formed between ChG and catechins. Catechins dissolved in NADES showed better antimicrobial activity than in water. . Agar diffusion method was unsuitable for evaluation antimicrobial activity of sample in NADES. .